Changes in Law, Changes in Teaching - Morales Luna, Félix (2005)
This article evaluates the type of teaching provided in Peruvian law schools. The author points out that the current training process follows the positivist tradition. This model conceives of the law as a system of rules, which implies fidelity to the law and its mechanical application to the concrete case. However, it is clear that this approach does not respond to a social reality that requires a change in the law. The consequence of following this traditional approach is that students often end up with an understanding of the law that does not correspond to legal reality and practice. For this reason, it is proposed to adopt a view of law as a social practice rather than a set of rules and principles. In this sense, following Atienza and Ruiz Manero, it is proposed that the teaching of law should abandon this positive paradigm and focus on a new theory of law based on a constitutionalist paradigm. This new vision conceives of law as a system that balances theory and practice, with particular emphasis on the latter. In this sense, this perspective provides guidelines for future professionals to orient their reasoning from the moment they become familiar with theoretical concepts to the resolution of a given case.